Theological Exclusivity In Islamic Monotheism: A Library Research Analysis On The Quranic Prohibition Do Not Set Up Rivals Unto Allah - Bukhari Moeslim; Muhammad Naufal Padhil Juniarta; Agung Pranoto Kadiatmaja (Imanu: Jurnal Hukum dan Peradaban Islam, 2025)
This study explores Islamic law, legal philosophy, and current Islamic culture, focusing on the idea of theological exclusivism in Islamic monotheism through the Qur'anic verse “Do not associate partners with Allah” (Qur’an 4:36). It examines the theological and legal consequences of tawhid, or divine unity, as the core principle for just practices in contemporary Islamic law. Utilizing a qualitative phenomenological method within a library-based research context, the research critically evaluates historical theological writings, interpretations of the Qur'an, and modern academic literature. Information was gathered through documentary analysis and processed using the Miles and Huberman interactive framework, which includes steps like reduction, categorization, and thematic analysis. The results highlight three main points: (1) tawhid forms the basis of legal and ethical exclusivity in Islam; (2) the ban on shirk maintains both spiritual purity and social stability; and (3) theological exclusivism offers a basis for a justice-oriented and God-centered understanding of law. The research concludes that an enhanced comprehension of theological exclusivism bolsters the knowledge foundation of Islamic law while adapting to contemporary civilizational changes. The implications include promoting education in law based on theology and the creation of religious policies that reconcile doctrinal clarity with social inclusiveness.